GWAS reveals new recessive loci associated with non- syndromic facial clefting (2012)
ABSTRACT: We have applied a GWAS to 40 consanguineous families segregating cases of non-syndromic cleft lip with or without cleft palate (NS CL/P) (a total of 160 affected and unaffected individuals) in order to trace potential recessive loci that confer susceptibility to this common facial malformation. Pedigree-based association test (PBAT) analyses reported nominal evidence of association and linkage over SNP markers located at 11q25 (rs4937877, P = 2.7 × 10−6), 19p12 (rs4324267, P = 1.6 × 10−5), 5q14.1 (rs4588572, P-value = 3.36 × 10−5), and 15q21.1 (rs4774497, P = 1.08 × 10−4). Using the Versatile Gene-Based Association Study to complement the PBAT results, we found clusters of markers located at chromosomes 19p12, 11q25, and 8p23.2 overcome the threshold for GWAS significance (P < 1 × 10−7). From this study, new recessive loci implicated in NS CL/P include: B3GAT1, GLB1L2, ZNF431, ZNF714, and CSMD1, even though the functional association with the genesis of NS CL/P remains to be elucidated. These results emphasize the importance of using homogeneous populations, phenotypes, and family structures for GWAS combined with gene-based association analyses, and should encourage. other researchers to evaluate these genes on independent patient samples affected by NS CL/P.